Different Types of Progressive Wave Solutions via the 2D-Chiral Nonlinear Schrödinger Equation - Osman, M. S.; Baleanu, Dumitru; Tariq, Kalim Ul-Haq; Kaplan, Melike; Younis, Muhammad; Rizvi, Syed Tahir Raza (Frontiers in Physics, 2020)
A versatile integration tool, namely the protracted (or extended) Fan sub-equation (PFS-E) technique, is devoted to retrieving a variety of solutions for different models in many fields of the sciences. This essay presents the dynamics of progressive wave solutions via the 2D-chiral nonlinear Schrödinger (2D-CNLS) equation. The solutions acquired comprise dark optical solitons, periodic solitons, singular dark (bright) solitons, and singular periodic solutions. By comparing the results gained in this work with other literature, it can be noticed that the PFS-E method is an useful technique for finding solutions to other similar problems. Furthermore, some new types of solutions are revealed that will help us better understand the dynamic behaviors of the 2D-CNLS model.